School maturity of pre-school age visually impaired children - Gudonis, Vytautas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The sample or research is 310 pre-school age visually impaired children. The average age of the surveyed is 6.3 years, the sharpness of vision is V 0.3–1. The research employed the methods for assessment of children’s maturity for school worked out by G. Gintilienė, D. Butkienė, S. Girdzijauskienė et al. (2005). During the investigation, essential problems of pre-school age visually impaired children have been estimated: a number of hyperactive children increases; also, a number of children who can hardly focus and retain attention increases; poor visual-motor coordination; narrow vocabulary; they explain notions of active vocabulary with difficulty. Results of school maturity of pre-school age visually impaired children proved significance of pre-school education institutions in visually impaired children’s preparation for school. It has been found that when surveying children of pre-school groups twice, in September and May, as well as preparing and using psychologists’ recommendations for pedagogues and parents, the level of pupils’ school maturity increases.